2010
DOI: 10.1002/da.20778
|View full text |Cite
|
Sign up to set email alerts
|

DBT-enhanced habit reversal treatment for trichotillomania: 3-and 6-month follow-up results

Abstract: DBT-enhanced HRT offers promise for improved long-term treatment results in TTM. Changes in TTM severity from baseline to 3-and 6-month follow-up is correlated with changes in emotion regulation capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 7 publications
0
52
0
2
Order By: Relevance
“…Nine (64.3%) subjects met criteria as treatment responders (≥35% reduction on the MGH-HPS and CGI improvement score of 1 or 2) at the end of the study [definition of responder as previously used in treatment studies (Dougherty et al 2006;Keuthen et al 2011)]. The mean effective dose of dronabinol was 11.6± 4.1 mg/day.…”
Section: Efficacy Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nine (64.3%) subjects met criteria as treatment responders (≥35% reduction on the MGH-HPS and CGI improvement score of 1 or 2) at the end of the study [definition of responder as previously used in treatment studies (Dougherty et al 2006;Keuthen et al 2011)]. The mean effective dose of dronabinol was 11.6± 4.1 mg/day.…”
Section: Efficacy Resultsmentioning
confidence: 99%
“…Controlled clinical trials evaluating potential pharmacological interventions for trichotillomania have demonstrated that N-acetyl cysteine (Grant et al 2009), olanzapine (Van Ameringen et al 2010), and clomipramine (Swedo et al 1993) all show some promise in reducing hair-pulling behavior. Similarly, psychosocial interventions, particularly cognitive behavioral therapy, have become established treatments for trichotillomania (Keuthen et al 2011;Woods et al 2006a, b;Diefenbach et al 2006), but few individuals seek these treatments or can find trained therapists. Despite their promise, these treatments do not appear effective for all individuals with trichotillomania, and so additional options are needed.…”
Section: Introductionmentioning
confidence: 98%
“…Expected correlations between ER capacity and hair pulling severity were demonstrated during both acute and maintenance treatment. At 3-and 6-month follow-up after the 3-month maintenance period, significant improvement from baseline still occurred for all hair pulling severity and ER measures (Keuthen et al, 2011). At both follow-up time points, significant correlations were reported between changes in hair pulling severity and ER capacity.…”
Section: Introductionmentioning
confidence: 84%
“…Our research group has been active in exploring the role of affective dysregulation in TTM (Shusterman, Feld, Baer & Keuthen, 2009) and the potential treatment efficacy of Dialectical Behavior Therapy (DBT)-enhanced habit reversal training (Keuthen et al, 2010(Keuthen et al, , 2011. Our findings from a large Internet survey of TTM demonstrated that hair pullers had more difficulty than normal controls in managing their emotions, with a small to moderate relationship between affective regulation and hair pulling severity (Shusterman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As hypothesized, the authors found signifi cant pre-to post-treatment improvement in emotion regulation occurred, and this improvement was correlated with reductions in hair pulling severity (Keuthen et al, 2010 ). Signifi cant improvement from baseline at 3-and 6-month follow-up was also found on the measures of hair pulling severity and total scale scores for emotion regulation measures (Keuthen et al, 2011 ).…”
Section: Chaptermentioning
confidence: 86%